Saints and Sites: The Interrelationship Between Church Dedications and Placenames in England - Adrian Room (Names, 1992)
Abstract A personal name in an English placename may be that of the saint to whom the local parish church is dedicated, as notably in Cornwall. Some church dedications, however, evolved from a misinterpretation of the placename. Conversely, some placenames apparently preserving a saint's name are actually based on a secular personal name, even when prefixed by St.